MANIPULATION OF FINANCIAL STATEMENTS - Amelia, Rizky Windar (KIAT BISNIS, 2017)
The role of a financial report in the presentation of financial statements, each institution or company that makes the report has desire to make âoutstandingâ financial statement in accordance with their interests. Nowadays, there are many cases in which both big and small companies deliberately âbeautifyâ the financial statements for the sake of the company itself. Basically, there are generally two main strategies in manipulating financial statements (financial shenanigans), like inflating and shrinking income.